Impact of insecticides on natural enemies of planthoppers in direct seeded rice - D, Dhyan Chowdary; G, Ramachandra Rao; T, Madhumathi; A, Jawahar Reddy (ORYZA-An International Journal of Rice, 2024)
In the kharif season of 2020, a field experiment was conducted at the Agricultural College Farm, Bapatla to evaluate the impact of some insecticides in combination with the neem products on natural enemies of planthoppers such as green miridbug, Cyrtorhinus lividipennis (Reuter) and spider Lycosa pseudoannulata (Boesenberg and Strand) and Tetragnatha maxillosa (Thorell) in direct seeded rice (DSR). The results concerning the influence of insecticidal treatments, on natural predators such as miridbugs and spiders revealed that neem formulation 1500ppm @ 5ml l-1 with 6.13 miridbugs/hill and 8.83 spiders/10 hills h were at par with the untreated control showing no adverse effects on the predators of rice planthoppers. Among the other treatments, dinotefuran 20SG @ 40g a.i. ha-1 has recorded lowest number of natural predators with 2.77 miridbugs/hill and 5.17 spiders/10 hills, followed by triflumezopyrim 10.6SC @ 25g a.i. ha-1 with 2.93 miridbugs/hill and 5.27 spiders/10 hills; Pymetrozine 50WG @ 150g a.i. ha-1 with 3.07 miridbugs/hill and 5.50 spiders/10 hills which differed significantly from the untreated control.